Ngupi Pai Culture in Coffee Shops: Media and Social Space in the Urban Society in Bandar Lampung - Nurdin, Bartoven Vivit; Sari, Ifaty Fadliliana; Mathis Corbin; Ghanyy, Rafly; Ramandha, Wulan Suci; Turki, Syifaa Sabianova Addina (The Journal of Society and Media, 2026)
This article examines the activity and cultural product of Ngupi Pai, a tradition of drinking coffee together within Lampung cultural heritage, which has experienced an expansion of meaning from a domestic activity commonly carried out at home (lamban) to one also conducted in public spaces such as coffee shops. This transformation occurs alongside the development of media, information technology, urbanization, and multicultural social environments in cities. This study employs a qualitative approach with data collected through in-depth interviews, participant observation, and documentation in Bandar Lampung. Data analysis was conducted using triangulation, peer review, and member checking to ensure the validity and credibility of the findings. The results show that Ngupi Pai has shifted from private to broader public spaces, where drinking coffee is no longer limited to consumption but has become a social trend of gathering in coffee-serving venues. Drawing on Douglas’s beverage construction theory, drinking practices possess sociocultural dimensions that contribute to social bonding, identity construction, and symbolic meaning production. Coffee functions as a medium that creates egalitarian and communicative interaction spaces, positioning coffee shops as arenas for tolerance, inter-ethnic harmony, and informal social diplomacy. This transformation strengthens the adaptive nature of Ngupi Pai within contemporary urban sociocultural dynamics